Respuesta :
Answer:
Step-by-step explanation:
1/3(12x+6x-21)
Take 1/3 of everything in the ()
4x+2x-7 combine like terms
6x-7
The equivalent expression is 6x - 7
Given the function 1/3(12x+6x-21), to get the equivalent expression, we will open the parenthesis using the distributive law;
= 1/3(12x+6x-21)
= 1/3(12x) + 1/3(6x) - 1/3(21)
= 4x + 2x - 7
On simplification, the resulting expression will be:
= 6x - 7
Hence the equivalent expression is 6x - 7
Learn more on functions here: https://brainly.com/question/19999031